The Inventory of Seagrasses in Marine Field Station of Faculty of Fisheries and Marine Science in Subdistrict of East Likupang District North Minahasa - Stevani Rawung; Ferdinand F Tilaar; Ari B Rondonuwu (Sam Ratulangi University, 2018)
This study was conducted in Marine Field Station of Faculty of Fisheries and Science of Sam Ratulangi University, Sub-district of East Likupang, North Minahasa. This study aims to identified the seagrasses in the water of Marine Field Station. The benefits of this study are for the database of seagrasses ecosystem management and comparative for other studies. The Observation and data collection was using random survey technic by analyzed the areas to collecting all the seagrass species found. Furthermore, the seagrass samples were categorised into each species. The result showed the amount of seagrass species in Marine Field Station are 8 species from 6 genera and 2 families: Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, Syringodium isoetifolium, Thalassia hemprichii, Enhalus acoroides, Halophila ovalis, dan Halophila minor.Keyword: Inventory, Seagrass, Marine Field Station ABSTRAKPenelitian dilakukan di perairan Marine Field Station Fakultas Perikanan dan Ilmu Kelautan Unsrat Kecamatan Likupang Timur Kabupatan Minahasa Utara. Tujuan penelitian untuk mengidentifikasi lamun yang ada di Perairan Marine Field station. Manfaat penelitian dapat menjadi data pengelolaan ekosistem padang lamun dan dapat menjadi perbandingan untuk penelitian-penelitian selanjutnya. Pengamatan dan pengambilan sampel menggunakan teknik survei jelajah, yaitu dengan menjelajahi wilayah pengamatan sambil mencari semua spesies lamun. Lamun yang diambil adalah semua jenis yang ditemui. Selanjutnya, sampel lamun dikelompokan berdasarkan spesies. Hasil pengamatan menunjukkan jumlah spesies lamun pada lokasi penelitian di Perairan Marine Field Station adalah 8 spesies dari 6 genera dan 2 famili yaitu, Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, Syringodium isoetifolium, Thalassia hemprichii, Enhalus acoroides, Halophila ovalis, dan Halophila minor. Kata kunci: Inventarisasi, Lamun, Marine Field Station